Respuesta :

Answer:

x = 13

Step-by-step explanation:

Step 1: Simplify both sides of the equation.

  • [tex](-2)(x) + (-2)(-5)= -16[/tex]
  • [tex]-2x + 10 =-16[/tex]

Step 2: Subtract 10 from both sides.

  • [tex]-2x + 10 - 10 = -16 - 10[/tex]
  • [tex]-2x = -26[/tex]

Step 3: Divide both sides by -2.

  • [tex]\frac{-2x}{-2}=\frac{-26}{-2}[/tex]
  • [tex]x = 13[/tex]

Step 4: Check if solution is correct.

  • [tex]-2(13-5)=-16[/tex]
  • [tex]-26 + 10 = -16[/tex]
  • [tex]-16=-16[/tex]

Therefore, x = 13.

Answer:

x=13

Step-by-step explanation:

-2(x -5) = -16

Divide each side by -2

-2(x -5)/-2 = -16/-2

x-5 = 8

Add 5 to each side

x-5+5 = 8+5

x=13